2002
DOI: 10.1021/ed079p248
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Student Understanding of General Chemistry with Concept Mapping

Abstract: Design of the Study Action Research ModelAction research was selected as an appropriate model for this study. Action research is a four-stage model of planning, action, observation, and reflection. Within each cycle, specific innovations are introduced within a course, data are collected and analyzed, and suitable revisions planned. Following each cycle of stages, the research continues by evaluating the outcome of the previous cycle, reorganizing, and proceeding through another cycle (7). Further details abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 14 publications
(22 reference statements)
3
65
0
1
Order By: Relevance
“…Results showed that students' level of differentiation, degree of connectivity among nodes, and the use of abstract concepts related to chemical processes increased with schooling. Wilson concluded that knowledge becomes more organized and interrelated with increasing expertise in a domain, corroborating previous expert‐novice results in other domains such as biology (Dauer, Momsen, Speth, Makohon‐Moore, & Long, ; Pearsall, Skipper, & Mintzes, ), chemistry (Francisco, Nakhleh, Nurrenbern, & Miller, ; Ruiz‐Primo, Schultz, Li, & Shavelson, ), engineering (Segalàs, Ferrer‐Balas, & Mulder, ), and medical education (Daley & Torre, ; West, Pomeroy, & Park, ).…”
Section: Background Literaturesupporting
confidence: 75%
“…Results showed that students' level of differentiation, degree of connectivity among nodes, and the use of abstract concepts related to chemical processes increased with schooling. Wilson concluded that knowledge becomes more organized and interrelated with increasing expertise in a domain, corroborating previous expert‐novice results in other domains such as biology (Dauer, Momsen, Speth, Makohon‐Moore, & Long, ; Pearsall, Skipper, & Mintzes, ), chemistry (Francisco, Nakhleh, Nurrenbern, & Miller, ; Ruiz‐Primo, Schultz, Li, & Shavelson, ), engineering (Segalàs, Ferrer‐Balas, & Mulder, ), and medical education (Daley & Torre, ; West, Pomeroy, & Park, ).…”
Section: Background Literaturesupporting
confidence: 75%
“…Observing the mean values for the students' achievement in [LQs] and [SSynQs] (Table 2), it was noted that students from both groups achieved better scores on conventional, linear questions, [LQs], than on systemically oriented questions, [SSynQs]. In order to explain these results, we have connected our findings with Francisco et al (2002) findings on students' achievement in concept maps chemistry problems. These authors (Francisco et al, 2002) stated that students need to organize their knowledge structure in appropriate way in order to successfully solve such problems.…”
Section: Analysis Of the Students' Achievementmentioning
confidence: 52%
“…In order to explain these results, we have connected our findings with Francisco et al (2002) findings on students' achievement in concept maps chemistry problems. These authors (Francisco et al, 2002) stated that students need to organize their knowledge structure in appropriate way in order to successfully solve such problems. Respectively, [SSynQs] could be successfully solved only if students have fully constructed meaningful understanding of concept.…”
Section: Analysis Of the Students' Achievementmentioning
confidence: 77%
“…It is a way of representing relations between ideas, images or words, in the same way that a sentence diagram represents the grammar of a sentence. Concept maps provide an excellent tool for students to generate meaningful connections between chemical concepts and they provide information about students' conceptual understanding, (Francisco, Nakhleh, Nurrenbern & Miller 2002;Cardellini, 2004).…”
Section: Introductionmentioning
confidence: 99%